Comparative Retrospective Study of Tension-Free Vaginal Mesh Surgery, Native Tissue Repair, and Laparoscopic Sacrocolpopexy for Pelvic Organ Prolapse Repair. (10th April 2020) - Kanasaki, Haruhiko; Oride, Aki; Hara, Tomomi; Kyo, Satoru
Abstract : Introduction and Hypothesis . Many would argue that sacrocolpopexy is the standard surgical procedure for pelvic organ prolapse (POP), but other surgical techniques were proposed and practically applying to the patients with POP. In this study, we compared postoperative outcomes of three surgical methods for POP repair. Methods . We identified that 308 women who had undergone surgical repair of POP were followed up for at least 6 months. Recurrence rates of POP after tension-free vaginal mesh (TVM) surgery ( n  = 243), native tissue repair (NTR) (vaginal hysterectomy with colpopexy, anterior and posterior colpoplasty, or circumferential suturing of the levator ani muscles and apical repair by transvaginal sacrospinous ligament fixation (SSLF)) (NTR; n  = 31), and laparoscopic sacrocolpopexy after subtotal hysterectomy (LSC; n  = 34) were compared. Presence of mesh erosion was also recorded. Results . Patients who underwent LSC were significantly younger (65.32 ± 3.23 years) than those who underwent TVM surgery (69.61 ± 8.31 years). After TVM surgery, the rate of recurrence (over POP-Q stage II) was 6.17% (15/243) and was highest in patients with advanced POP. The recurrence rate in patients who underwent NTR procedure was 3.23% (1/34) and that in patients who underwent LSC was 11.76% (4/11). There was no statistically significant difference in the recurrence rate between the three types of surgery. There were 13 cases (5.35%) of mesh erosion after TVM surgery and none after LSC surgery. The risk of mesh erosion was correlated with having had total TVM surgery but not with patient age or POP stage. Repeat procedures were performed in 5 women (2.14%) who underwent TVM surgery and 1 (2.94%) who underwent LSC. No patient underwent repeat surgery after NTR. There was no statistically significant difference in the reoperation rate between the three types of surgery. Conclusion . Our study suggested that TVM surgery, NTR, and LSC have comparable outcomes as for the postoperative recurrence rate and mesh erosion. However, the outcomes of each technique need to be carefully evaluated over a long period of time.